A viewpoint based approach to the visual exploration of trajectory. (August 2017) - Li, Jie; Xiao, Zhao; Kong, Jun
Abstract: We present a new viewpoint-based approach to improving the exploration effects and efficiency of trajectory datasets. Our approach integrates novel trajectory visualization techniques with algorithms for selecting optimal viewpoints to explore the generated visualization. Both the visualization and the viewpoints will be represented in the form of KML, which can be directly rendered in most of off-the-shelf GIS platforms. By playing the viewpoint sequence and directly utilizing the components of GIS platforms to explore the visualization, the overview status, detailed information, and the time variation characteristics of the trajectories can be quickly captured. A case study and a usability experiment have been conducted on an actual public transportation dataset, justifying the effectiveness of our approach. Comparing with the basic exploration approach without viewpoints, we find our approach increases the speed of information retrieval when analyzing trajectory datasets, and enhances user experiences in 3D trajectory exploration.